Learning Process Management at PKBM RA Abata Mardhotillah Karawang - Muhammad Ferri; Ilham Fahmi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
This study examines and analyzes the Management of the Learning Process at PKBM RA Mardhotillah Karawang. PKBM itself can be categorized as a non-formal education unit that provides educational services such as formal education. So that it fulfills the prerequisites in carrying out the learning process at PKBM RA Abata Mardhotillah Karawang. The research method used is the descriptive qualitative research method. And this data collection technique uses interview, observation, and documentation techniques. The results of this study indicate that the management of the PKBM RA Abata Mardhotillah Karawang learning process has shown systematic governance, this is evidenced by a number of learning programs implemented in the annual program plan and the preparation of daily implementation schedules.